Effect of the Application of 1-Methylcyclopropene and Wax Emulsions on Proximate Analysis and Some Antioxidants of Soursop (Annona muricata L.) - Cristina L. Moreno-Hernández; Sonia G. Sáyago-Ayerdi; Hugo S. García-Galindo; Miguel Mata-Montes De Oca; Efigenia Montalvo-González (The Scientific World Journal)
The effect of the application of 1-methylcyclopropene (1-MCP) and wax emulsions, alone or combined, on composition analysis, vitamin C, polyphenols, and antioxidant capacity of soursop was evaluated. Fruits were stored as follows: at 25°C (control), and at 16°C: fruits sprayed with candelilla or flava emulsions, fruits treated with 1500 nL/L of 1-MCP (20°C, 12 h), and fruits treated with 1-MCP and then sprayed with emulsions. Fruits were allowed to ripen and the edible part was used for analysis. Only fruits stored at 16°C without 1-MCP showed visible symptoms of chilling injury. Fruits treated with 1-MCP combined with flava emulsion maintained in greater extent their vitamin C content, dietary fiber, total phenolics content, and antioxidant activity. The combination of 1-MCP and emulsions can be utilized in postharvest handling of soursop because this combination can preserve its nutritional composition and antioxidant activity.